Towards a Collective Approach of Immersive 3D Servicescape in the Metaverse Experience: Insights from Thematic Content Analysis - Lee, Tae-Hee; Kwon, Gyu-Hyun; Han, Jieun (International JOURNAL OF CONTENTS, 2025)
This study synthesizes the current landscape of servicescape research within the context of the metaverse, identifying future academic challenges for the evolution of immersive 3D servicescapes. The research highlights key trends, gaps, and emerging themes in the field by utilizing a comprehensive thematic content analysis of existing literature review data and insights from focus group interviews with metaverse experts. Findings reveal that metaverse-related research in the field of servicescape has been proposed in five directions: (a) dynamics between physical and virtual servicescapes, (b) redefining servicescape measurements for the metaverse, (c) evolving the s-o-r framework, (d) personalization and adaptation of extended reality environment, and (e) necessity of domain-specific approach. The study proposes a roadmap for future investigations, contributing to the academic discourse by providing a nuanced understanding of immersive 3D servicescapes and suggesting strategic directions for further research. KCI Citation Count: 0